Multidisciplinary Management of Giant Fetal Sacrococcygeal Teratom - Bıldırcın, Devran; Alper, Tayfun; Bıçakçı, Ünal; Erdoğan, Özgür; Tosun, Miğraci; Altunsoy, Süleyman; Çelik, Handan (Gynecology Obstetrics & Reproductive Medicine, 2009)
Sacrococcygeal Teratoma (SCT) is one of the most frequent tumors of the newborn period. SCT is seen in varying sizes, and there is a relationship between the size and the clinical course. Postoperative prognosis of SCT with a low malign potential is good in the newborn period. Prenatal follow-up and postnatal management are rather important. We described our patient who was diagnosed in the early weeks and followed up till week 37, and then was given birth by caesarean section. The hemodynamic findings were stabilized during the newborn period. the patient was successfully operated by pediatric surgeons to restore her health.